A Foreign Body (Gossypiboma) in Pregnancy: Report of the First Case in the Pregnancy - Cem Dane; Murat Yayla; Banu Dane; Ahmet Çetin (Medical Network, 2006)
Gossy piboma is a rare tumor caused by gauze fibers retained during surgery. To our knowledge, a gossy piboma in the abdomen in pregnancy has not been previously reported in the literature. A 27-year-old woman at 38 weeks of gestation was presented with adnexial mass. A caesarean delivery had been performed 5 years ago. Obstetrics ultrasonography showed thick curvilinear hyperechoic band with distal acoustic shadowing in the pubic region. In caesarean section, a well-encapsulated, brownish sof t-tissue tumor containing serous fluid was discovered in the central cavity, shown at histological investigation to be gauze fibers. The frequency incidence is not very well known; however general estimation is 1 in 1000 to 15000 f or intra-abdominal operations. The best prevention of this condition can be achieved by meticulous count of surgical materials and also by routine use of surgical textile materials impregnated with a radio-opaque marker.